Increased homozygosity in the first Hispanic patient with plantar lipomatosis, unusual facies, and developmental delay (Pierpont syndrome): a case report. (December 2016) - O'Keefe, Siobhán; Wefuan, Dieter; Humberson, Jennifer; Schmidt, Karen; Wiley, John
Abstract Background Pierpont syndrome was first described in 1998 with key characteristics including developmental delay, dysmorphic facial features, fat pads on hands and feet, and feeding difficulties. To date the mechanism of inheritance is unknown. Nine out of ten previously described patients with Pierpont syndrome were boys. This is the first report of a case of a non-white patient with Pierpont syndrome and she is the second female patient to be described as having Pierpont syndrome. Case presentation Our patient is a 16-month-old Hispanic girl with extreme developmental delay, microcephaly, large ears, short and thick upper lip, broad philtrum, widely spaced teeth, constipation, dysphagia, fat pads on feet and hands, autistic behavior and seizure-like episodes. She had a normal karyotype (46, XX), and array testing showed greater than 8 % homozygosity with otherwise normal results. Genes within these areas of homozygosity may provide clues to an etiology and suggest autosomal recessive inheritance. This case report highlights the possibility of ethnic variations in this syndrome's presentation, which may have ramifications in uncovering the pathogenesis as well as expanding the phenotype. Conclusion Pierpont syndrome should be considered in the evaluation of children with the described features, regardless of their gender and ethnicity.